2017
DOI: 10.1111/ocr.12154
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional skeletal mandibular changes associated with Herbst appliance treatment

Abstract: Objectives Three-dimensional evaluation of skeletal mandibular changes following Herbst appliance treatment. Setting and Sample Population Retrospective case–control study, based on a sample size calculation. Twenty-five pubertal patients treated with Herbst appliance (HAG), and 25 matched Class II patients who received other non-orthopaedic dental treatments (CG). Material and Methods Three-dimensional models were generated from pre-treatment (T0) and post-treatment (T1) cone beam computed tomograms. Volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 24 publications
1
26
1
5
Order By: Relevance
“…The results agree with earlier conventional 2D studies that observed increases in mandibular length in patients treated with the Herbst appliance [9,[24][25][26]. The observed effect on condylar growth is also similar to that reported by Souki et al, who showed in 3D that the net growth of the condyles in all surfaces was significantly greater in the Herbst group [22]. The results indicate a true stimulation of bone apposition at the condyles, and ultimately may help maximize the skeletal outcome by generating substantially more growth in the sagittal dimension.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results agree with earlier conventional 2D studies that observed increases in mandibular length in patients treated with the Herbst appliance [9,[24][25][26]. The observed effect on condylar growth is also similar to that reported by Souki et al, who showed in 3D that the net growth of the condyles in all surfaces was significantly greater in the Herbst group [22]. The results indicate a true stimulation of bone apposition at the condyles, and ultimately may help maximize the skeletal outcome by generating substantially more growth in the sagittal dimension.…”
Section: Discussionsupporting
confidence: 92%
“…As the morphological changes during each of the observation time periods contain both normal growth and changes due to treatment, the normal growth process that contributes to the correction must be factored out to evaluate the skeletal effect due to the appliance. Only two studies have evaluated in 3D the additional skeletal effects on the mandible by comparing patients treated with the device with control groups undergoing one phase nonorthopedic dental treatment [8,22]. Like previous 2D studies, these have led to disparate conclusions in terms of the mandibular length, largely because obtaining a standardized control group is challenging in retrospective studies as it is hard to match the follow-up time precisely.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies evaluated the skeletal and dental effects of the Herbst appliance (2)(3)(4)(8)(9)(10)(11). However, few studies (12,13) verified whether the device causes alveolar bone loss in the region of the lower incisors.…”
Section: Introductionmentioning
confidence: 99%
“…LeCornu et al showed significant bone remodelling activity within the glenoid fossae of HA patients. Souki et al found a significant increase and change in the pattern of bone remodelling and a different magnitude and direction of condylar growth after HA treatment. However, bone remodelling processes, both from the condyles and/or the glenoid fossae, cannot explain the extensive drift and repositioning of the condyle within the glenoid fossa after 8 or 12 months of treatment, following mandibular advancements ranging from 4 to 10 mm.…”
Section: Discussionmentioning
confidence: 99%